Kinetics and mechanism of the ozone reaction with alcohols, ketones, ethers and hydroxybenzenes - Rakovsky, Slavcho; Anachkov, Metody; Belitskii, Mikhail; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2016)
The review, based on 92 references, is focused on degradation of organics by ozonation and it comprises various classes of oxygen-containing organic compounds – alcohols, ketones, ethers and hydroxybenzenes. The mechanisms of a multitude of ozone reactions with these compounds in organic solvents are discussed in details, presenting the respective reaction schemes. The corresponding kinetic parameters are given and some thermodynamic parameters are also listed. The dependences of the kinetics and the mechanism of the ozonation reactions on the structure of the compounds, on the medium and on the reaction conditions are revealed. Various possible applications of ozonolysis are specified and discussed. All these reactions have practical importance for the protection of the environment. В огляді, що базується на 92 посиланнях, розглянуто руйнування органічних речовин внаслідок озонування та стосується різних класів кисневмісних органічних сполук – спиртів, кетонів, етерів та гідроксибензенів. Обговорено механізми реакції цих сполук з озоном в органічних розчинниках і представлені відповідні схеми реакції. Приведені кінетичні і деякі термодинамічні параметри. Показано залежність кінетики та механізму реакції озонування від структури сполук, середовища і умов реакції. Зазначено і обговорено різні можливості застосування озонолізу. Наведені реакції мають практичне значення для захисту навколишнього середовища.
Кінетика і механізм реакції озону з спиртами, кетонами, етерами і гідроксибензенами
Keywords: ozonation; alcohol; ketone; ether; hydroxybenzene; kinetics; mechanism; озонування; спирт; кетон; етер; гідроксибензен; кінетика; механізм